Prevalence of chronic kidney diseases and determinants among TDF users of pregnant and lactating women based on eGFR-cg, and MDRD-4 in hospital setting of north east Amhara, Ethiopia - Gebretsadikk, Eyob; Hadush, Azmach; Hussien, Mohammed; Asres, Getahun (International Journal of Health, 2018)
In recent days, it is common to see increasing incidence of Fanconi, proximal kidney tubular damage and chronic kidney diseases-CKD among high risk populations that drew the clinicians’ attention to monitor closely. Among these risk populations with potential CKD incidence; HIV positive patients who uses TDF as a component of HAART need to be monitored for the incidence of CKD as a toxicity of TDF before initiation and during treatment despite the fact that the current monitoring practice in Ethiopia in most hospitals remain to be poor. Hence this study aimed at measuring the incidence of CKD among high risk segment of HIV positive pregnant and lactating women who uses TDF as part of their HAART treatment. Using a non-proportionate stratified sampling, a total of 111 HIV+ pregnant and lactating women who are on TDF based HAART treatment were enrolled to measure the incidence of CKD based on NKF K/DOQI Classification. Using the Android application of Medicalc GFR-cg, and MDRD-4; the prevalence of stage-2 CKD was 16.2 % (60-89 ml/min) and Stage 5-CKD/Renal Failure who require dialysis were 3.6% (CrCl < 15ml/min/1.72m2) by both method of calculation CrCl (GFR-cg and MDRD-4). Women who were lactating had a relative risk of 0.918 (95% CI lies within 0.845-0.998) of acquiring CKD (P= 0.045). The other associated factors were BMI less than 18.5 (P= 0.004 and adjusted OR of 7.82), WHO clinical stage-1 (P=0.014, odds ratio of 5.4 and 95% CI of 1.24-24.42), baseline CD4 count > 500 (P=0.02), and duration on TDF (> 12 months on treatment) and low haematocrit of 30 had a higher risk of falling into Stage 2 CKD with cohort risk estimate of 4.103 (95 % CI of 1.02, 16.54). The risk estimate of WHO stage 2 to acquire stage-4 CKD was 1.087 (95% CI of 1.002, 1.180) statistically significant (P=0.05.). The prevalence of stage 2 CKD among pregnant and lactating women by GFR-cg method of calculation was higher than MDRD-4 calculation. In this study, MDRD-4 method underestimated stage 2 CKD. Hence it is worth and highly recommended to use GFR-cg method in the baseline and during treatment monitoring of TDF toxicity to the kidney particularly for diagnosing the early stage of CKD.